Respuesta :
2(x + 5) + 4 (x - 9) = -14
multiply the first bracket by 2
(2)(x)=2x
(2)(5)=10
multiply the second bracket by 4
(4)(x)=4x
(4)(-9)=-36
2x+10+4x-36=-14
2x+4x+10-36=-14 ( combine like terms)
6x+10-36=-14
6x-26=-14
move -26 to the other side
sign changes from -26 to +26
6x-26+26=-14+26
6x=14+26
6x=12
divide both sides by 6 to get x by itself
6x/6=12/6
Cross out 6 and 6, divide by 6 and then becomes 1*1*x=x
divide by 6 for 12/6
12/6=2
6/6=1
2*1=2
Answer:
x=2
Answer:
x = 12
Step-by-step explanation:
Perform the indicated multiplications:
2x + 10 + 4x - 36 = -14
Combine the x terms: 6x + 10 - 36 = -14
Combine the constants on the right side: 6x = 12
Dividing both sides by 6, we get x = 12.